The Name of a Saint Disclosed and Established through Iconography - Nana Gonjilashvili, (The Kartvelologist - A Bilingual Peer-reviewed, Academic Journal of Georgian Studies, 2014)
None of the old Georgian sources from the the century to the 1830's mentions the name of 'Sidonia', the sister of Elioz, who brought the Lords' tunic from Jerusalem to Mtskheta. Sidonia is not depicted or mentioned either on the murals, miniatures, or icons dating back to the 9th to 13th and also the 17th to 19th centuries that represent the erection and ascension of the living pillar or on the seals of the catholicoses of the 17ht and 18th centuries, or the flag of Vakhtang VI. In the stories of Life of Saint Nino, published in the 19th century, Elioz's sister is mostly referred to as 'Sidonia', and the understanding is that she is well known to Georgians. In Teimuraz Bagrationi's work - The History of Iveria from the Origins ..., for the first time in 19 centuries, we encounter the name of Sidonia, the sister of Elioz and the embracer of the Lord's tunic. The placement of the name 'Sidonia' in brackets at the mention of Elioz's sister in Nikoloz Gulaberidze's Sakitkhavi (The Reader), which was included in M. Sabinin's book Georgia's Paradise and the mentioning the name of Elioz's sister on the icon The Glory of the Holy Orthodox Church of Georgia greatly contributed to the popularization and establishment of the name of Elioz's sister - 'Sidonia.'